Dampak Banjir Terhadap Masyarakat di Kota Tanjungpinang (Studi Kasus: Perumahan Taman Harapan Indah Tanjungpinang Timur) - Susilawati Susilawati; Fitria Monalisa; R. Dinda Elsa Zulfina (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
Flooding is a disaster that often occurs in Tanjungpinang City and has a significant impact on the community, including the Taman Harapan Indah Tanjungpinang Timur Housing Complex. This research aims to identify the impact of flooding on the community in the Taman Harapan Indah Tanjungpinang Timur Housing Complex and efforts that can be made to reduce the impact. The method used is a case study with data collection techniques through interviews and field observations. The research results show that the impact of flooding includes loss of material, time, health, stress and uncertainty. Efforts that can be made to reduce the impact of flooding include improving the drainage system, building embankments, regulating drainage systems, creating flood canals, and revising development layouts. Communities and governments can work together to reduce the impact of flooding by increasing awareness about the importance of having a good drainage system and environment, cleaning the environment, and improving the drainage system. The government can also build embankments and monitor the drainage system.